Cadamba: A miraculous tree having enormous pharmacological implications - Dwevedi, Alka; Sharma, Kuldeep; Sharma, Yogesh K (Pharmacognosy Reviews)
The Cadamba is one of the important medicinal plants belonging to the Rubiaceae family. It is crucially significant as it has the largest number of phytochemicals and secondary metabolites (viz., cadambagenic acid, cadamine, quinovic acid, β‑sitosterol, cadambine, etc.) having pharmacological and biological properties. It can be used as an alternative to various synthetic chemical compounds in the prevention as well as the treatment of several incurable diseases. More than 100 years of research has been done to discover various phytochemicals and their implications. Very few of them, i.e. ≤2% have been commercialized due to the lack of a suitable model system as well as various associated controversial issues. The solubility of phytochemicals is another major concern: Further response that will be generated due to the solvent used is also unpredictable. Moreover, the Cadamba is one of the ornamental plants with religious significance. Here we have made an effort to summarize all the phytochemicals and their significance to render the interest that would help in their commercialization.
Keywords: Anticancer; antioxidant; Cadamba; pharmacology; phytochemical